Determinants of quality of life and psychological status in adults with psoriasis - Kwan, Zhenli; Bong, Yii Bonn; Tan, Leng Leng; Lim, Shu Xian; Yong, Adrian Sze Wai; Ch'ng, Chin Chwen; Tan, Maw Pin; Ismail, Rokiah (Springer, 2018)
We investigated whether disease severity and clinical manifestations were associated with depression, anxiety, stress and quality of life in adults with psoriasis. Participants were recruited from a dermatology outpatient clinic at a teaching hospital. Information on sociodemographic characteristics, disease severity, presence of arthropathy and head involvement was specifically recorded. Disease severity was assessed using the Psoriasis Area and Severity Index (PASI). Quality of life and psychological symptoms were measured using the Dermatology Life Quality Index (DLQI) and the Depression Anxiety Stress Scale (DASS), respectively. One hundred individuals were recruited. Unadjusted analysis revealed that head involvement was associated with depression [odds ratio (OR) 8.509; 95% confidence interval (CI) 1.077–67.231] and anxiety (OR 6.46; 95% CI 1.401–29.858). Severe disease was associated with a poorer quality of life compared to mild disease (OR 3.750; 95% CI 1.330–10.577). Younger age was associated with an increased risk of depression [mean difference (MD) − 8.640; 95% CI − 16.390 to − 0.890], anxiety (MD − 11.553; 95% CI − 18.478 to− 4.628), stress (MD − 11.440; 95% CI − 19.252 to − 3.628) and severely impaired quality of life (MD − 12.338; 95% CI − 19.548 to − 5.127). Following adjustments for age and disease severity, anxiety, stress and depression remained associated with severely impaired quality of life.